Dynamic Voltage Stability Evaluation of Power Systems Considering Industrial Electrical Loads - Mohammad Reza Ansari (Majlesi Journal of Electrical Engineering)
This paper presents a simulation of the dynamic voltage stability in power system. In application of modern power system, dynamic assessment of voltage stability is known as basic concept. In order to study dynamic voltage stability in a power system, different dynamic boundaries are defined such as, Hopf bifurcation (HB) boundary. HB point is an oscillatory boundary in power system. For recognition of the bifurcations, it is unavoidable to study the eigenvalues of power system. In spite of this, determination of these eigenvalues need to dynamic Jacobian matrix of power system and modal analysis that is very time consuming and complex in large systems. Also, different industrial loads (static and dynamic) e.g. induction motors can effect on dynamic voltage stability boundaries. In this paper, we proposed a solution method based on analysis the eigenvalues of reduced Jacobian matrix and time domain simulation for assessment of dynamic voltage stability. In addition, effects of industrial electrical loads on the small disturbance voltage stability are evaluated by the proposed method. To show the effectiveness of the proposed solution method, it is tested on IEEE 14 bus and New England test systems.